2018
DOI: 10.1016/j.combustflame.2018.02.028
|View full text |Cite
|
Sign up to set email alerts
|

The combustion kinetics of the lignocellulosic biofuel, ethyl levulinate

Abstract: Combustion and Flame Rights NOTICE: this is the author's version of a work that was accepted for publication in Combustion and Flame. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Combustion and Flame,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…These RD processes produce 100 kmol h −1 EL (equivalent to about 120 kt year −1 ) with a purity of 99.5 mol% (same as for water by‐product). This is consistent with the purity values reported in previous studies about the design of EL processes, and in the context of using EL as a fuel bio‐additive …”
Section: Approach and Methodologysupporting
confidence: 92%
“…These RD processes produce 100 kmol h −1 EL (equivalent to about 120 kt year −1 ) with a purity of 99.5 mol% (same as for water by‐product). This is consistent with the purity values reported in previous studies about the design of EL processes, and in the context of using EL as a fuel bio‐additive …”
Section: Approach and Methodologysupporting
confidence: 92%
“…Alternatively, ethanol can be recovered from ethyl‐glucopyranoside by placing the solubilized product in hydrolytic conditions, followed by fermentation of the resulting glucose and recycling of the ethanol. Ethyl levulinate is a promising biofuel additive …”
Section: Introductionmentioning
confidence: 99%
“…Considered as one of the future platform chemicals, levulinic acid can be used in various applications, including fuel production . Several studies have shown that ethyl levulinate, an ester derived from levulinic acid, is a potential alternative of second‐generation biofuels or biofuel additives . Lei et al have reported successful engine tests of various blends of ethyl levulinate and ethyl levulinate/n‐butanol with a diesel fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Koivistoet al conducted a study for ignition engine and observed a reduction on overall particulate mass when ethyl levulinate is used as a fuel component. Ghosh et al studied gas phase combustion kinetics of ethyl levulinate and concluded that it is more suitable as a gasoline component than a diesel fuel. Wang et al compared the physical and chemical properties, performances, and emissions of ethyl levulinate‐biodiesel‐diesel and n‐butanol‐biodiesel‐diesel blends.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation